Comparison of voltage source converters and Z-source converters for electric vehicles - Ozkilic, Selin Ozcira; Dursun, Cagatay (EMERALD GROUP PUBLISHING LTD, 2021)
Voltage source and current source converters are used in industrial applications as either boost or buck converters for a defined power flow direction. These operational modes limit these converters to be utilized on their own in hybrid and electric vehicle (EV) applications. Z-source (impedance source) converters, on the other hand, have the capability to be operated as buck and boost converters to have a wide range of output levels. The boost ratio of the direct current link voltage of a Z-source converter is set by short-circuiting the phase legs of the converter and defining the overlap duration at each switching period. In order to have the optimum efficiency with the lowest possible total harmonic distortion, a modified space vector pulse width modulation method with an impedance network could be selected for closed-loop control of the quasi-resonant Z-source converter to drive permanent magnet synchronous motors (PMSMs). In this study, closed-loop vector-controlled drive systems built with two-level and three-level boosted voltage source converter topologies and two- and three-level quasi Z-source converters for field-oriented control of a PMSM in EV motor drive applications were compared under constant motor speed-constant load, constant speed-variable load and variable speed-constant load operating conditions.
Keywords: computational studies; semi-conductors; simulation; DESIGN; Materials Science